2018
DOI: 10.1159/000484631
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness with Swept-Source Optical Coherence Tomography versus Foveal Morphology in Young Children with a History of Prematurity

Abstract: Aim: Comparison of choroidal thickness (CT) and foveal morphology as seen with swept-source optical coherence tomography (SS-OCT) in children with a history of treated or spontaneously regressed retinopathy of prematurity (tROP or srROP) to assess the impact on best-corrected visual acuity (BCVA). Methods: CT was measured by SS-OCT (DRI-OCT Triton; Topcon, USA) single scans of a 6-mm diameter around the fovea in 17 children with tROP or srROP (4–7 years of age) and compared to 25 controls (age-matched children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In addition, Bowl et al. () observed a 22% thinner choroid in spontaneously regressed ROP and a 53% thinner choroid in treated ROP when compared to age‐matched full‐term children. Interestingly, Marques et al () showed that the number of days of oxygen exposure was the most significant negative predictive factor for CT. On the other hand, Fieß et al.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Bowl et al. () observed a 22% thinner choroid in spontaneously regressed ROP and a 53% thinner choroid in treated ROP when compared to age‐matched full‐term children. Interestingly, Marques et al () showed that the number of days of oxygen exposure was the most significant negative predictive factor for CT. On the other hand, Fieß et al.…”
Section: Discussionmentioning
confidence: 98%
“…A possible functional correlate to the calculated structural minification of INL and OPL structures could be the attenuation of cone mediated multifocal ERG (mfERG) responses within the fovea observed in the macula of preterms with and without ROP in a number of recent studies [30][31][32][33]. Since the mfERG response in a cone-initiated activity mainly reflects bipolar cell activity [34] it is possible that the decreased space available for the synaptic networks within OPL and INL is related to the reduced mfERG signals.…”
Section: Discussionmentioning
confidence: 99%
“…ese studies demonstrated a thinner choroid in premature infants that develop severe ROP; however, only the central choroidal thickness was evaluated and most of these studies were conducted in older age groups than our cohort [9,10]. Since the central retina is typically vascularized in most premature infants, this study concentrated more on evaluating the peripheral choroid of which, we believe, may be more involved in the development of ROP [2,3].…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have evaluated the choroidal thickness in premature infants using OCT [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation